The influence of nutrition on the formation and modification of human immunity - Zuzanna Chęcińska-Maciejewska; Andrzej Ciborek; Ewelina Książek; Hanna Krauss (Journal of Health Inequalities)
Human immunity is an important aspect of health, and it is integral to defence mechanisms against infections and diseases. At the same time, nutrition plays a role in providing the body with essential nutrients, which not only form the body’s basic building blocks but also influence the effectiveness of the immune system. The aim of this study was to review the available scientific research and literature in medicine, nutrition, and immunology to understand the effects of diet and nutrients on immune system function. A review of the scientific literature was conducted, analysing available evidence on the impact of diet on the immune system. The main dietary factors, such as vitamins, minerals, amino acids, antioxidants, and the gut microbiota, which play an essential role in regulating and enhancing immunity, were presented in this study. The importance of adequate nutrition for the development and function of the immune system was discussed. The role of vitamins and minerals, especially vitamins C and D, and zinc, in maintaining effective immunity was highlighted, and nutritional strategies supporting a healthy immune system were presented. Another important aspect was the analysis of the impact of the gut microbiota on immunity. Evidence was presented that diet can shape the composition of the gut microbiota, which directly impacts immune system function. Aspects of the Mediterranean diet and its effect on the immune system are presented. Adequate nutrition is crucial for shaping and modifying the human immune system. A diet rich in adequate nutrients and supporting a healthy gut microbiota can contribute to strengthening the immune system, which is important for preventing disease and maintaining health. Research into the impact of nutrition on the immune system is yielding new dietary strategies for preventing and treating immune-related diseases.